We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
294
1
avatar+266 

 Jan 6, 2016

Best Answer 

 #1
avatar+102320 
+10

Note that we have this matrix equation :

 

Ax  = b        where A =   [5  -2             and     b = [ 2

                                        2  -1]                             -4]                       

 

If I multiply both sides of the equation [on the left] by the inverse of A, we have

 

(A-1) (A )x  =( A-1 ) b

 

But    (A-1) (A)  is just the Identity matrix,  I

 

So.....the left side just simplifies to  x .......and we have

 

x = A-1 b

 

So.....we just   need to find the inverse of A  = A-1

 

Note, for a 2 x 2 matrix  in the form of      [ a     b

                                                                   c     d ]

 

The inverse is given by :    [1/ (ad - bc)] *  [  d   - b    =

                                                                    - c    a]

 

[1 / (-5 +4)] * [ -1  2     =     [-1] [ -1  2

                        -2  5]                   -2  5]

 

So.....the inverse of A   =  [1    - 2    

                                           2    -5]  

 

So......

 

x = A-1 * b     =     [ 1    - 2   *    [2             =          

                              2    -5 ]       -4]                  

 

 

   [1*2  +    -2*-4      =    [ 2 +8        =  [10

    2*2  +  - 5* -4 ]           4 +20]           24]

 

So....the last matrix is the answer.......

 

And that's it !!!!

 

 

 

cool cool cool

 Jan 6, 2016
edited by CPhill  Jan 6, 2016
edited by CPhill  Jan 6, 2016
edited by CPhill  Jan 6, 2016
edited by CPhill  Jan 6, 2016
 #1
avatar+102320 
+10
Best Answer

Note that we have this matrix equation :

 

Ax  = b        where A =   [5  -2             and     b = [ 2

                                        2  -1]                             -4]                       

 

If I multiply both sides of the equation [on the left] by the inverse of A, we have

 

(A-1) (A )x  =( A-1 ) b

 

But    (A-1) (A)  is just the Identity matrix,  I

 

So.....the left side just simplifies to  x .......and we have

 

x = A-1 b

 

So.....we just   need to find the inverse of A  = A-1

 

Note, for a 2 x 2 matrix  in the form of      [ a     b

                                                                   c     d ]

 

The inverse is given by :    [1/ (ad - bc)] *  [  d   - b    =

                                                                    - c    a]

 

[1 / (-5 +4)] * [ -1  2     =     [-1] [ -1  2

                        -2  5]                   -2  5]

 

So.....the inverse of A   =  [1    - 2    

                                           2    -5]  

 

So......

 

x = A-1 * b     =     [ 1    - 2   *    [2             =          

                              2    -5 ]       -4]                  

 

 

   [1*2  +    -2*-4      =    [ 2 +8        =  [10

    2*2  +  - 5* -4 ]           4 +20]           24]

 

So....the last matrix is the answer.......

 

And that's it !!!!

 

 

 

cool cool cool

CPhill Jan 6, 2016
edited by CPhill  Jan 6, 2016
edited by CPhill  Jan 6, 2016
edited by CPhill  Jan 6, 2016
edited by CPhill  Jan 6, 2016

20 Online Users

avatar
avatar
avatar